Lewis Acid-Catalyzed Rearrangement of Fluoroalkylated Propargylic Alcohols: An Alternative Approach to β-Fluoroalkyl-α,β-enones - Ramasamy, Manickavasakam; Lin, Hui-Chang; Kuo, Sheng-Chu; Hsieh, Min-Tsang (Synlett, 2019)
A practical Lewis acid-catalyzed Meyer–Schuster rearrangement of fluoroalkylated propargylic alcohols, leading to a series of β-fluoroalkyl-α,β-enones, is developed. The methodology reported herein features moderate to high yields and high stereoselectivity in the synthesis of β-alkyl-β-fluoroalkyl-α,β-enones.
Keywords: Lewis acids; Meyer–Schuster rearrangement; β-trifluoromethyl-α,β-enones; metal triflates; fluorinated compounds